Eyes: conduit to COVID-19, relevance of eye protection, and face shield in ophthalmology waiting areas - Rajan Sharma; Mamatha Balakrishna; Parul Chawla; Nagesha K Chokkahalli; Ashok Sharma; Rekha Gyanchand; Jagat Ram (Asian Journal of Medical Sciences, 2022)
COVID-19 pandemic caused by highly contagious Severe Acute Respiratory Syndrome Coronavirus 2 has affected the health and economy of the population worldwide. A major route of transmission of coronavirus is through respiratory system by aerosols and microdroplets. Virus can also spread by direct or indirect touching of the inmate objects harboring live virus. Virus can gain access through the nasal and oral ororopharyngeal mucosa. Coronavirus has been isolated from the ocular surface and tearfilm. Severe Acute Respiratory Syndrome Coronavirus 2 has been documented to drain from the ocular surface to oropharyngeal mucosa through tears. In the preventive measures, the mask acts as a barrier to touch and aerosol transmission and its use has been advocated all over the world. Transmissions through eyes (ocular surface and tear film) are possible, however, compared to the aerosol transmission the risk may be small. The use of glasses, safety goggles and face shields may provide protection to eyes from contamination and minimizes the risk of transmission from the ocular surface and tear film. In this review, the authors aim to highlight the role of the ocular surface and tear film in the transmission and possible measure to prevent the infection through the eyes.